Reprogramming brain-resident macrophages: from disease drivers to therapeutic allies in neurological disorders - Zhao, Peng; Li, Su-Yi; Liu, Qun; Peng, Xiao-Chun; Liu, Lian; Yang, Fu-Yuan; Wang, Chao; Qian, Feng; Tang, Feng-Ru (Frontiers in Cellular Neuroscience, 2026)
Brain-resident macrophages (BRMs), including microglia and border-associated macrophages (BAMs), are the core immune sentinels of the central nervous system (CNS). They originate from early embryonic yolk sac and fetal liver progenitors and maintain their population throughout life via self-renewal. During neurodevelopment, microglia maintain neural network homeostasis by phagocytosing apoptotic neural precursors and pruning synaptic connections. In adulthood, they rapidly respond to infection, injury, or protein aggregation, which can both promote repair and exacerbate neurotoxicity. BAMs, located in the meninges, perivascular spaces, and choroid plexus, play a key role in boundary homeostasis and peripheral immune signal surveillance. Recent studies reveal that BRMs exhibit dual roles in Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), multiple sclerosis (MS), as well as ischemic stroke, traumatic brain injury, and radiation-induced brain injury: they can protect neurons by clearing pathological proteins or cellular debris, but persistent inflammatory responses may drive neurodegeneration. In AD, microglia clear Aβ plaques via triggering receptor expressed on myeloid cells 2 (TREM2) and ADGRG1 signaling, while BAMs regulate synaptic damage and cerebrovascular function through CD36-ROS and SPP1 pathways. In PD and HD, BRMs contribute to α-synuclein- and mutant huntingtin-related inflammatory responses. In MS, BRMs modulate the pro−/anti-inflammatory balance through antigen presentation and cytokine signaling. Based on these mechanisms, therapeutic strategies targeting BRM functions are emerging, including NLRP3 inflammasome inhibitors, TREM2 agonists, and interventions promoting microglial neuroprotective phenotypes. Future approaches aiming to precisely modulate BRM plasticity and their interactions with the peripheral immune system may transform these immune sentinels from “disease drivers” to “therapeutic allies,” offering novel strategies for treating neurodegenerative diseases and brain injuries.